Lake Woebe guaranteed: Misuse of Test Scores in Massachusetts, Part I - Haney, Walt (Education Policy Analysis Archives, 2002)
Misuse of test results in Massachusetts largely guarantees woes for both students and schools. Analysis of annual test score averages for close to 1000 Massachusetts schools for four years (1998—2001) shows that test score gains in one testing period tend to be followed by losses in the next. School averages are especially volatile in relatively small schools (with less than 150 students tested per grade). One of the reasons why scores fluctuate is that the Massachusetts state test has been developed using norm-referenced test construction procedures so that items which all students tend to answer correctly (or incorrectly) are excluded from operational versions of the test. This article concludes with a summary of other reasons why results from state tests, like that in Massachusetts, ought not be used in isolation to make high-stakes decisions about students or schools.